Controlled drug release characteristics and enhanced antibacterial effect of graphene nanosheets containing gentamicin sulfate - Pandey H.; Parashar V.; Parashar R.; Prakash R.; Ramteke P.W.; Pandey A.C. (My University, 2025)
A novel methanol derived graphene (MDG) and gentamicin sulfate nanohybrid was prepared, and the loading and release behaviour of gentamicin on MDG is investigated. An efficient drug loading of 2.57 mg mg-1 was obtained at pH 7. By applying release kinetic models, the mechanism of release of the drug from the MDG matrix was found to be following the Korsmeyer-Peppas model. However, the diffusional release exponent (n) value lies below 0.5 demonstrating that the mechanism controlling the drug release is the Fickian diffusion. © 2011 The Royal Society of Chemistry.